Shigella-mediated immunosuppression in the human gut: subversion extends from innate to adaptive immune responses - Katja Brunner; Fatoumata Samassa; Philippe J. Sansonetti; Armelle Phalipon (Taylor & Francis Group, 2019)
The enteropathogen, Shigella, is highly virulent and remarkably adjusted to the intestinal environment of its almost exclusive human host. Key for Shigella pathogenicity is the injection of virulence effectors into the host cell via its type three secretion system (T3SS), initiating disease onset and progression by the vast diversity of the secreted T3SS effectors and their respective cellular targets. The multifaceted modulation of host signaling pathways exerted by Shigella T3SS effectors, which include the subversion of host innate immune defenses and the promotion of intracellular bacterial survival and dissemination, have been extensively reviewed in the recent past. This review focuses on the human species specificity of Shigella by discussing some possible evasion mechanisms towards the human, but not non-human or rodent gut innate defense barrier, leading to the lack of a relevant animal infection model. In addition, subversion mechanisms of the adaptive immune response are highlighted summarizing research advances of the recent years. In particular, the new paradigm of Shigella pathogenicity constituted of invasion-independent T3SS effector-mediated targeting of activated, human lymphocytes is discussed. Along with consequences on vaccine development, these findings offer new directions for future research endeavors towards a better understanding of immunity to Shigella infection.